Empirical analysis of language learning strategies for optimizing online language courses - Lip, Rashidah; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Kar Mee, Cheong; Poh Ee, Tan; Ismail, Nurmaisarah; Mohd Yusoff, Azizul; Lestari, Uning; Ahmad Fesol, Siti Feirusz (Institute of Advanced Engineering and Science, 2024)
In today’s changing education world, online language classes are becoming more important. Recognizing the important role of the relationship between language learning strategies and students’ preferences, our empirical study examines the patterns or factors that explain the observed correlations among variables to provide insights in optimizing online language courses. Addressing a critical gap in the existing literature that has traditionally treated language learning strategies and online language education as distinct entities, our survey-based research collected comprehensive data from students enrolled in online language courses. Focused on six key language learning strategies: memory, cognitive, compensation, metacognitive, affective, and social. The research shows a delicate connection between these strategies and students’ preferences in online teaching mode. The empirical findings provide insights into certain strategies that work better for specific online learning methods. This helps us grasp the varied preferences of groups of students. This research enriches online language education by revealing an unexplored connection between strategies and preferences and provides a valuable resource for educators and course designers. The information given helps make online language classes better. It ensures that students learn languages more effectively online, considering their functional and practical needs in online learning.